Interactive 3D Wi-Fi Display Miracast System using Back Channel Input - S Raghunatha Reddy, B; P Ramana Reddy, Dr. (International Journal of Engineering and Technology, 2018)
With advances in multimedia technology, 3D video is driving lot of attention these days. Delivery of 3D video over communication networks poses additional technical challenges by virtue of having multiple video views and the perception of depth. In this paper, we present an interactive multi-view video 3D Wi-Fi Display Miracast system that enables adaptive transmission of ongoing 3D video content based on userâ€™s input, fed from the back channel, in real time. Proposed solution enables 3D video transmission of desired views only. Solution gives the viewers the best 3D experience by way of selective sharing the suitable views, yet with significant reduction in bandwidth and power consumption requirements. Â Â Â